Currency convertibility, capital markets and monetary management : some paradignms from Southern Africa and the Caribbean. - CLARKE, Lawrence (1996)
Highlights key similarities and differences between fourteen Commonwealth Caribbean countries, and ten Southern African countries. Surveys the capital market scene in Southern Africa and the Caribbean, and examines the issue of currency convertibility and some implications for monetary management in the two regions.